A tale of two cities: Comparison of impacts on CO2 emissions, the indoor environment and health of home energy efficiency strategies in London and Milton Keynes. (November 2015) - Shrubsole, C.; Das, P.; Milner, J.; Hamilton, I.G.; Spadaro, J.V.; Oikonomou, E.; Davies, M.; Wilkinson, P.
Abstract: Dwellings are a substantial source of global CO2 emissions. The energy used in homes for heating, cooking and running electrical appliances is responsible for a quarter of current total UK emissions and is a key target of government policies for greenhouse gas abatement. Policymakers need to understand the potential impact that such decarbonization policies have on the indoor environment and health for a full assessment of costs and benefits. We investigated these impacts in two contrasting settings of the UK: London, a predominantly older city and Milton Keynes, a growing new town. We employed SCRIBE, a building physics-based health impact model of the UK housing stock linked to the English Housing Survey, to examine changes, 2010–2050, in end-use energy demand, CO2 emissions, winter indoor temperatures, airborne pollutant concentrations and associated health impacts. For each location we modelled the existing (2010) housing stock and three future scenarios with different levels of energy efficiency interventions combined with either a business-as-usual, or accelerated decarbonization of the electricity grid approach. The potential for CO2 savings was appreciably greater in London than Milton Keynes except when substantial decarbonization of the electricity grid was assumed, largely because of the lower level of current energy efficiency in London and differences in the type and form of the housing stock. The average net impact on health per thousand population was greater in magnitude under all scenarios in London compared to Milton Keynes and more beneficial when it was assumed that purpose-provided ventilation (PPV) would be part of energy efficiency interventions, but more detrimental when interventions were assumed not to include PPV. These findings illustrate the importance of considering ventilation measures for health protection and the potential variation in the impact of home energy efficiency strategies, suggesting the need for tailored policy approaches in different locations, rather than adopting a universally rolled out strategy. Highlights: We model current the (2010) and future (2050) housing of London and Milton Keynes. We apply a range of building interventions and grid decarbonisation scenarios. We investigate impacts on energy use, indoor temperatures, pollutants and health. Results vary appreciably both between locations and the direction of health impacts. Locationally tailored policy approaches are needed to achieve CO2 reduction targets.